Routine hematological profile in tuberculosis patients undergoing treatment at Bakunase Community Health Center, Kupang City - Yoan Novicadlitha; Ni Made Susilawati; Jevenich BN Runumeha (Science Midwifery, 2026)
Tuberculosis is a disease caused by the bacterium Mycobacterium tuberculosis (M. tuberculosis). Anti-tuberculosis drugs are effective in killing Mycobacterium tuberculosis but may also have side effects on various organs, particularly the hematological system. Monitoring through laboratory examinations, particularly hematological tests, can help prevent complications of other diseases. This descriptive study aimed to determine the hematological profile of tuberculosis patients undergoing treatment at the Bakunase Public Health Center in Kupang City. The population in this study comprised TB patients receiving anti-tuberculosis therapy at the Bakunase Public Health Center in Kupang City, with a total sample of 30 patients. The sampling technique used was purposive sampling. The results showed that TB patients at Bakunase Public Health Center were predominantly male (56.7%), in the productive age group of 19–59 years (83.3%), and mainly in the intensive phase of treatment (0–2 months) (60%). In the productive age group, most hematological parameters were within normal limits, particularly erythrocytes, platelets, hemoglobin, and MCHC. Meanwhile, in the non-productive age group, fewer patients had normal hematological values. Based on treatment duration, patients in both the intensive and continuation phases generally had hematological values within normal limits, although percentages varied.